KETERLAMBATAN PENANGANAN LAPORAN MASYARAKAT OLEH KOMISI YUDISIAL DALAM PERSPEKTIF PERBUATAN MELAWAN HUKUM OLEH PENGUASA (ONRECHTMATIGE OVERHEIDSDAAD) - Rahayu Susanti; Tata Wijayanta; Mailinda Eka Yuniza (Jurnal Yudisial, 2025)
Professionalism in public service delivery is a prerequisite for every state institution, including the Judicial Commission, in following up public complaint reports concerning alleged violations of the Code of Ethics and Judicial Conduct (KEPPH). This study examines Judgment Number 405/Pdt.G/2023/PN.Smg concerning a claim of onrechtmatige overheidsdaad filed against the Judicial Commission arising from delays in handling public complaint reports. This study aims to analyze the judicial reasoning in determining whether the alleged lack of professionalism of the Judicial Commission may be classified as onrechtmatige overheidsdaad. The study also analyzes the corrective measures undertaken by the Judicial Commission to address factors that cause delays in handling public reports in the future. This study employs normative legal research using a case approach. The findings indicate that the panel of judges did not explicitly base its reasoning on the doctrine of onrechtmatige overheidsdaad. Instead, the judicial reasoning primarily focused on the Judicial Commission’s institutional status as a state institution responsible for public service delivery. The panel of judges found indications of a lack of professionalism based on evidence demonstrating delays and procedural deviations in handling public reports. The study further shows that the Judicial Commission has implemented improvements by streamlining report-handling procedures through revisions to its internal regulations and strengthening its digital-based report-handling system. These measures are intended to improve the efficiency, transparency, and accountability of public service delivery. These measures reflect Judicial Commission’s commitment to administrative reform to prevent recurring delays in handling public reports while continuously improving the quality of public service delivery.